Prognostic Significance of High-Sensitivity Cardiac Troponin-T in Non-ST Elevation Myocardial Infarction - Ahsan Ali, Madia Ayaz Malik, Sardar Bilal Mehboob Abbasi, Mohammad Amir Khan, Muhammad Tayyab, Shumaila Israr (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Non-ST elevation myocardial infarction (NSTEMI) remains a major cause of morbidity and mortality, with substantial variability in outcomes. High-sensitivity cardiac troponin-T (hs-cTnT) is the biomarker of choice for diagnosis, but its role as a prognostic marker in predicting in-hospital complications and adverse outcomes requires further evaluation. Objective: To assess the prognostic significance of hs-cTnT levels in patients admitted with NSTEMI. Methods: This prospective observational study enrolled 155 patients with NSTEMI at Punjab Institute of Cardiology from January 2023 to June 2023. Patients were stratified into tertiles based on admission hs-cTnT levels (low, intermediate, high). Baseline demographics, comorbidities, hemodynamic and ECG parameters, and left ventricular ejection fraction were recorded. Outcomes assessed included recurrent ischemia, heart failure, arrhythmia, urgent revascularization, in-hospital mortality, major adverse cardiovascular events (MACE), and length of hospital stay. Results: Patients with higher hs-cTnT were older (66 vs. 57 years, p=0.002), more often diabetic (58% vs. 35%, p=0.04), and had lower LVEF (45.7% vs. 52.1%, p<0.001). Killip class II–IV was present in 61.5% of high hs-cTnT patients compared to 11.5% in the low group (p<0.001). In-hospital complications were significantly more frequent in the high group: recurrent ischemia (25% vs. 8%), heart failure (33% vs. 6%), arrhythmias (15% vs. 2%), urgent revascularization (27% vs. 10%), and mortality (17% vs. 2%) (all p<0.05). MACE occurred in 67% of high hs-cTnT patients compared with 15% in the low group (p<0.001). Hospital stay was longer in the high group (7.1 vs. 4.1 days, p<0.001). Conclusion: Elevated hs-cTnT levels are strongly associated with adverse in-hospital outcomes in NSTEMI patients, including higher complication rates, longer hospital stay, and increased MACE. hs-cTnT provides independent prognostic value beyond traditional risk factors and should be incorporated into early risk stratification and management pathways for NSTEMI. Keywords: NSTEMI, high-sensitivity troponin-T, prognosis, MACE, in-hospital outcomes, risk stratification